Digitalization of Tradition: An Android-Based Gamelan Degung Sundanese Application to Improve Musicianship Skills is Higher Education - Maulana, Marsel Ridky; Sukmayadi, Yudi; Sunaryo, Ayo; Tresnadi, Soni (Institut Seni Indonesia Yogyakarta, 2025)
Using the Gamelan Degung Sunda application as an alternative instructional medium has proven effective in addressing the challenges posed by the limited availability of gamelan instruments in higher education settings. The demand for flexible and efficient solutions in developing performance skills for Gamelan Degung has driven the integration of digital technology into arts education. This study adopts a qualitative approach using a case study method, employing direct observation and in-depth interviews with students who engaged with the application as part of their learning process. The findings indicate that the Gamelan Degung Sunda application effectively enhances students' understanding of musical structure and fundamental techniques in playing Gamelan Degung Sunda. It also significantly improves accessibility by enabling students to practice independently outside formal classroom sessions. Moreover, the application fosters active learning, despite its limited content scope, which does not fully represent the complexity of karawitan (Sundanese classical music). These findings underscore that integrating digital technology into arts education is not merely a short-term solution to infrastructural constraints but represents an innovative approach to cultivating adaptive and participatory learning experiences. The practical implication lies in the application's role as a pedagogical aid within academic environments that lack adequate facilities. Academically, the study opens avenues for developing digitally-based arts curricula and further investigating the effectiveness of application-based instructional media within the context of arts education in the digital transformation era. Future application developments are recommended to include more complex instructional content and comprehensive integration within technology-oriented arts study programs.Digitalisasi Gamelan Degung: Aplikasi Berbasis Android untuk Meningkatkan Kemampuan Musikal di Pendidikan TinggiAbstrakPemanfaatan aplikasi Gamelan Degung Sunda sebagai media pembelajaran alternatif terbukti mampu menjawab tantangan keterbatasan instrumen gamelan di lingkungan perguruan tinggi. Kebutuhan akan solusi yang fleksibel dan efisien dalam mengembangkan keterampilan memainkan Gamelan Degung mendorong integrasi teknologi digital dalam proses pendidikan seni. Studi ini menggunakan pendekatan kualitatif dengan metode studi kasus, melalui observasi langsung dan wawancara mendalam terhadap mahasiswa yang menggunakan aplikasi tersebut dalam pembelajaran. Hasil menunjukkan bahwa aplikasi Gamelan Degung Sunda efektif dalam mendukung pemahaman struktur musikal dan teknik dasar dalam bermain Gamelan Degung Sunda, sekaligus meningkatkan aksesibilitas mahasiswa untuk berlatih secara mandiri di luar kelas formal. Aplikasi ini juga memotivasi proses belajar secara aktif, meskipun masih memiliki keterbatasan dalam cakupan materi yang belum merepresentasikan keseluruhan kompleksitas karawitan Sunda. Temuan ini menunjukkan bahwa integrasi teknologi digital dalam pembelajaran seni bukan hanya solusi jangka pendek atas keterbatasan sarana, tetapi juga pendekatan inovatif dalam menciptakan pengalaman belajar yang adaptif dan partisipatif. Implikasi praktisnya terletak pada pemanfaatan aplikasi ini sebagai alat bantu pedagogis dalam lingkungan akademik yang memiliki keterbatasan fasilitas. Sementara itu, implikasi akademiknya membuka peluang untuk pengembangan kurikulum seni berbasis digital serta kajian lebih lanjut mengenai efektivitas media pembelajaran berbasis aplikasi dalam konteks pendidikan seni di era transformasi digital. Disarankan pengembangan lanjutan terhadap konten aplikasi dengan materi yang lebih kompleks, serta integrasi menyeluruh dalam program studi seni berbasis teknologi.Kata kunci: media pembelajaran; aplikasi musik; gamelan degung Sunda; aplikasi digital gamelan degung.